2003
DOI: 10.1194/jlr.m300182-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

FXR-mediated down-regulation of CYP7A1 dominates LXRα in long-term cholesterol-fed NZW rabbits

Abstract: We investigated how cholesterol feeding regulates cholesterol 7 ␣ -hydroxylase (CYP7A1) via the nuclear receptors farnesoid X receptor (FXR) and liver X receptor ␣ (LXR ␣ ) in New Zealand white rabbits. After 1 day of 2% cholesterol feeding, when the bile acid pool size had not expanded, mRNA levels of the FXR target genes short-heterodimer partner (SHP) and sterol 12 ␣ -hydroxylase (CYP8B) were unchanged, indicating that FXR activation remained constant. In contrast, the mRNA levels of the LXR ␣ target genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…35,36 Under normal conditions, high concentrations of cholesterol in tissue stimulate oxysterol production, and the oxysterols, as well as cholesterol, downregulate cholesterol biosynthesis 37 by inhibiting HMGCR, the rate-limiting enzyme in the cholesterol biosynthetic pathway. In McA-RH7777 hepatomas, however, HMGCR was markedly upregulated despite the increased concentrations of both oxysterols and cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Under normal conditions, high concentrations of cholesterol in tissue stimulate oxysterol production, and the oxysterols, as well as cholesterol, downregulate cholesterol biosynthesis 37 by inhibiting HMGCR, the rate-limiting enzyme in the cholesterol biosynthetic pathway. In McA-RH7777 hepatomas, however, HMGCR was markedly upregulated despite the increased concentrations of both oxysterols and cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…We know that CYP7A1 in the liver and FXR in the ileum and liver is up-and downregulated in these models ( 8,9 ). Thus, these models are appropriate for studying the relationship between the expression of ileal FGF15/19 and the protein levels of the gut-hepatic signal in the portal blood, as well as the expression of CYP7A1 in the liver.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…It has been reported that rodents have a very hydrophilic bile acid pool, which is less potent in activation of FXR; thus, the LXRα could function as an important regulator of CYP7A1 in mice (Chiang et al, 2001). In contrast, CYP7A1 expression was down-regulated by a high-cholesterol diet in African green monkeys (Rudel et al, 1994) and in rabbits (Xu et al, 2003), since the inhibitory effect of FXR may override the stimulatory effect of LXRα. There are another Figure 7.…”
Section: Discussionmentioning
confidence: 71%